Bicycle lane planning : a site appraisal in Fukuoka, Japan - Syakir Amir Ab Rahman,; Lukman Hakim Mahamod,; Muhammad Afiq Hakimi Ismail,; Wan Muhammad Hafizi Wan Mansor,; Safwan Sharit,; Muhammad Hafizi Zukrey,; Muhammad Hafizuddin Hanafi,; Muhammad Alif Khidhir Mohammad Aidid,; M. Zainora Asmawi,; Zakiah Ponrahono,; Nor Nadiah Najib, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cycling is one of the most sustainable modes to commute from one place to another. However, not everyone views bicycles as a fundamental component of the overall transportation system because presently, societies are heavily reliant on private vehicles. In reality, most see it only as a tool for recreational and exercise purposes. This paper seeks to identify the planning and design of bicycle lanes in Fukuoka, Japan. The research applies the site appraisal technique which involves gathering information about comparable site values within four areas i) Hakata station, ii) Ohori Park and Nishi Park, iii) Island city and iv) Fukuoka residential area. The findings identified various policies, guidelines and designs for bicycle infrastructure in Japan. There are significant differences between bicycle road, bicycle lane and sidewalks in Japan and Malaysia. Some of the findings show that Japan is gearing towards an even more bicycle friendly environment with the promulgation of the Promotion of Bicycle Use Act. However, there are also some setbacks such as the ineffectiveness of colored lanes to differentiate between bicycle lanes and pedestrian or vehicle lanes. Malaysia needs a blueprint and guidelines at the state and local levels to designate bicycle lanes and guarantee users’ safety and enjoyment. A specific unit for cycling in transportation related agencies is proposed to make Malaysia a bicycle-friendly city.